2017
DOI: 10.1021/acsami.7b16206
|View full text |Cite
|
Sign up to set email alerts
|

Novel Reduced Graphene Oxide/Zinc Silicate/Calcium Silicate Electroconductive Biocomposite for Stimulating Osteoporotic Bone Regeneration

Abstract: In the absence of external assistance, autogenous healing of bone fracture is difficult due to impaired regeneration ability under osteoporosis pathological conditions. In this study, a reduced graphene oxide/zinc silicate/calcium silicate (RGO/ZS/CS) conductive biocomposite with an optimal surface electroconductivity of 5625 S/m was prepared by a two-step spin-coating method. The presence of lamellar apatite nanocrystals on the surfaces of the biocomposite suggests that it has good in vitro biomineralization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 73 publications
(116 reference statements)
0
28
0
Order By: Relevance
“…However, in the presence of the biocomposite extracts with different dilution ratios, mesh-like circle structures were observed, indicating that HUVEC proliferation increased and expression of angiogenesis-related genes was promoted. These results indicated that the electroconductive biocomposite developed by Xiong et al [15] demonstrated superior in vitro osteogenesis and angiogenesis performances, displaying a large potential for stimulating osteoporotic bone regeneration. Although promising, application of this biocomposite to osteoporotic fracture healing will require further in vitro and in vivo studies, moving beyond the seeding of cells at the surface of the scaffolds.…”
Section: Bone Regenerationmentioning
confidence: 84%
See 4 more Smart Citations
“…However, in the presence of the biocomposite extracts with different dilution ratios, mesh-like circle structures were observed, indicating that HUVEC proliferation increased and expression of angiogenesis-related genes was promoted. These results indicated that the electroconductive biocomposite developed by Xiong et al [15] demonstrated superior in vitro osteogenesis and angiogenesis performances, displaying a large potential for stimulating osteoporotic bone regeneration. Although promising, application of this biocomposite to osteoporotic fracture healing will require further in vitro and in vivo studies, moving beyond the seeding of cells at the surface of the scaffolds.…”
Section: Bone Regenerationmentioning
confidence: 84%
“…Considering that bone defects may also arise from diseases such as osteoporosis (predominant disease due to the aging population), Xiong et al [15] explored the development of an electroconductive biocomposite for stimulating bone regeneration under osteoporosis conditions. Previous promising results have demonstrated that silicate-based biomaterials are able to be used in the enhancement of osteoporotic bone regeneration [16][17][18][19][20].…”
Section: Bone Regenerationmentioning
confidence: 99%
See 3 more Smart Citations